Biodegradable Zein-Based Blend Films: Structural, Mechanical and Barrier Properties - Pena Serna, Carolina [UNESP]; Lopes Filho, Jose Francisco [UNESP] (Faculty Food Technology Biotechnology, 2015)
The effect of adding a hydrocolloid on the structural, mechanical and barrier properties of zein-based blend films is evaluated. Zein-oleic acid blend film with added xanthan gum (Z-OA-XG) showed higher water solubility (13.09 %) and opacity (8.49 AU/mm) than zein-oleic acid (Z-OA) film (10.80 % and 5.19 AU/mm, respectively). Furthermore, Z-OA film had greater flexibility with lower Young's Modulus (YM=5.02 MPa) and higher elongation at break (eta=10.62 %); nonetheless, it was less resistant to tension (tensile strength sigma=8.5 MPa) than Z-OA-XG film, which showed YM, eta and sigma of 6.38 MPa, 6.66 % and 10.485 MPa, respectively. Both films had glossy and homogeneous structure with comparable water vapour and oxygen barrier properties around 4.39.10(-11) and 1.82.10(-13) g/(Pa.s.m), respectively. Based on that, xanthan gum structure influenced mainly mechanical and light barrier properties of zein-oleic acid blend films.
Keywords: blend film; biodegradable material; permeability; microstructure; tensile properties